Raven tales. Rough face girl [videorecording (DVD)] - Kientz, Chris, 1967- (Indigenous Collection., 2011)
After Dza is made fun of for being a girl, Frog tells her the story of Rough Face, a young girl who showed the people of her village that true beauty lies within.